Global Commodity Price Spillovers and Domestic Demand Dynamics in Indonesia: An Empirical Analysis - Nurfitri Martaliah; Asti Harkeni; Linda Trismi A; Veni Hardianti; Fitchi Utama Dewi; Muhammad Ikhwan Afdloli (Universitas Muria Kudus, 2025)
Global commodity prices have experienced high volatility over the past decade due to structural shifts in global demand, geopolitical tensions, the COVID-19 pandemic, and the ongoing energy transition. As an open economy, Indonesia is highly vulnerable to external shocks, which can influence domestic demand through price and exchange rate transmission mechanisms. This study aims to analyze the spillover effects of global commodity price fluctuations on Indonesia’s domestic demand, focusing on three key commodities—crude oil, coal, and cinnamon—over the 2015–2024 period.The research employs a Vector Error Correction Model (VECM) using annual time series data. This model allows for simultaneous analysis of short- and long-run relationships between global prices, domestic prices, exchange rates, per capita income, and domestic demand. Stationarity was tested using the Augmented Dickey–Fuller (ADF) test, cointegration through the Johansen method, and dynamic analysis using Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD).The results reveal a significant long-run relationship between global commodity prices and domestic demand in Indonesia. In the short run, increases in global and domestic prices significantly reduce domestic demand, whereas per capita income has a positive effect. The IRF analysis indicates that global price shocks produce the strongest negative response on domestic demand in periods 2–3 before gradually stabilizing. FEVD results show that global prices contribute the largest share (38.2%) to long-term variations in domestic demand.These findings confirm that global price volatility plays a crucial role in shaping Indonesia’s domestic demand dynamics. Therefore, policies aimed at stabilizing domestic energy prices, strengthening exchange rate management, diversifying strategic commodities, and boosting household income are essential to maintain purchasing power and enhance economic resilience.